Interpellation Mechanism In Jian Rong’s Wolf Totem - Yudhanita Pertiwi; Sri Saraswati; Yanuaresti Kusuma Wardhani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This paper explores the concept of ideology through the lens of Louis Althusser's theories, particularly interpellation, experienced by Chen Zen in Jiang Rong’s Wolf Totem. The purpose of this research is to go beyond oversimplified ideas of false consciousness and investigate how ideology essentially influences people's worldviews, directs group behaviour, and pervades every facet of human existence, from government system to personal identities. The research was carried out using descriptive qualitative method. It meticulously analyzes the novel Wolf Totem by Jiang Rong to demonstrate Althusser's concepts in practice. The results and discussion focus on how the protagonist, Chen Zhen, a Han Chinese student in Inner Mongolia, experiences a profound ideological shifting. Through his engagement in Mongolian culture and his observations of wolves, Chen's previous